Translation of metaphors in ex machina from English to Indonesian - Nafiza, Syakira; Erwina, Emmy (International Journal Linguistics of Sumatra and Malay, 2025)
This reserach investigates the translation of conceptual metaphors from English to Indonesian in the movie Ex Machina, utilizing a descriptive qualitative methodology.  The research seeks to categorize the types of metaphors included in the movie, examine the translation of these metaphors in the Indonesian subtitles, and assess the efficacy of the translation procedures in preserving the original conceptual meaning.  The principal data comprises English dialogues with metaphorical terms along with their respective Indonesian subtitles, chosen for their pertinence to Conceptual Metaphor Theory. The researcher used Lakoff & Johnson (1980) framework to sort each of the 10 metaphors into structural, orientational, or ontological metaphors. The researher used Miles & Huberman (1994) interactive approach to analyze the data. This model includes data reduction, data display, and making conclusions.  Molina & Hurtado Albir (2002) translation technique framework helped with the classification and analysis by finding strategies including literal translation, modification, and paraphrase.  The results indicate that numerous conceptual metaphors experience alterations in meaning as a result of cultural and language disparities, whereas others are maintained by meticulous lexical selections.  The predominant approaches discovered underscore the translator's efforts to reconcile meaning retention with naturalness in the target.  This research enhances comprehension of metaphor translation in audiovisual media and underscores the necessity of amalgamating cognitive linguistic theory with translation methodologies to guarantee precise and significant subtitle translation.